On the subgenus Eurysunius Reitter of Türkiye XI. Two new species from central eastern Anatolia (Coleoptera: Staphylinidae: Paederinae, Astenus) - Anlaş Si̇nan (Zootaxa, 2026)
Two species of the subgenus Eurysunius Reitter (Coleoptera: Staphylinidae: Paederinae: Astenus) from central eastern Anatolia in Türkiye are herein described and illustrated: Astenus bingolense sp. nov. from Bingöl Province and A. suphanicus sp. nov. from Bitlis and Ağrı provinces. With these additions, the subgenus is currently represented in Türkiye by 33 species, 32 of which are endemic to the country. Updated distributional data for the species from Türkiye are provided, and their occurrences within Türkiye are presented on a map.